PERTANGGUNGJAWABAN PIDANA KURATOR PELAKU TINDAK PIDANA PEMALSUAN SURAT DALAM PENGURUSAN HARTA PAILIT - Ade Nandar Silitonga; Tofik Yanuar Chandra; Mohamad Ismed (CORPUS JURIS : JURNAL ILMU HUKUM, 2025)
In recent years, there has been growing concern regarding indications of an increase in the practice of document forgery committed by certain curators in the context of bankruptcy administration. This study aims to examine and analyze the forms of criminal acts of document forgery in the administration of bankruptcy by curators, as well as the criminal liability of curators who commit such offenses. The theoretical framework employed in this research includes the theory of criminal liability and the theory of punishment. The results of the study indicate that the forms of criminal acts of document forgery in bankruptcy administration by curators include the creation of fictitious documents, alteration of authentic documents, manipulation of receipts, asset value manipulation, and the use of false deeds or creditor lists with the intent to deceive or mislead relevant parties. These actions not only harm creditors and disrupt the lawful distribution of bankruptcy assets but also undermine the integrity of the bankruptcy process, causing economic and moral losses. The criminal liability of curators for these acts is absolute and personal, as curators, in addition to violating the provisions of Articles 263, 264, or 266 of the Criminal Code, also betray their pro justitia mandate and fiduciary duties as guarantors (Garantenstellung) of the bankruptcy estate. The intentionality (dolus) of such acts, along with their impact on creditors and the bankruptcy system, aggravates the severity of the misconduct. Therefore, professional independence does not confer immunity; rather, it serves as an aggravating factor, making criminal sanctions necessary to uphold justice, provide deterrence, protect the bankruptcy system, and maintain broader socio-economic stability